1969
DOI: 10.1111/j.1365-2621.1969.tb10368.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Catalyzed Reactions as Influenced by Inert Gases at High Pressures

Abstract: The activities of tyrosinase, invertase, trypsin and chymotrypsin were studied after exposure to one or more of the following high-pressure inert gases: N20 at 600 psig or NI or Ar each at 5000 psig. Exposure to high-pressure nitrogen or argon failed to significantly inhibit the rate of tyrosinase activity in fluid systems. However, the rates of tyrosinase-catalyzed reactions in shell-cast gelatin gels were significantly depressed by exposure to high-pressure nitrogen, and even more so by high-pressure nitrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…Fujii et al (2002) reported that addition of argon accelerated the inactivation of Bacillus cereus spores at 20 C under the pressure of 600 MPa due to argon clathrate hydrates information. Behnke (1969) suggested that high pressure inert gases inhibit tyrosinase in non-fluid (i.e. gelatin) systems by decreasing oxygen availability.…”
Section: Introductionmentioning
confidence: 98%
“…Fujii et al (2002) reported that addition of argon accelerated the inactivation of Bacillus cereus spores at 20 C under the pressure of 600 MPa due to argon clathrate hydrates information. Behnke (1969) suggested that high pressure inert gases inhibit tyrosinase in non-fluid (i.e. gelatin) systems by decreasing oxygen availability.…”
Section: Introductionmentioning
confidence: 98%
“…Behnke et al (1969) also demonstrated that high pressure inert gases inhibited tyrosinase systems by decreasing oxygen availability rather than by physical alteration of the enzyme. When noble gases dissolve in water, enzymatic reactions are inhibited, resulting in restrained vegetable metabolism (Zhang et al, 2008).…”
Section: Resultsmentioning
confidence: 93%
“…Partly purified tyrosinase (PPO) was inhibited by noble gases including argon (Doebbler and others 1967; Behnke and others 1969; Spencer and others 1998; Zhang and others 2001). Ebert and Hornsey (1958) proposed that inert gases compete with oxygen for cellular sites; however, inhibition by noble gases was also found for some non‐oxygen dependant enzymatic reactions (Behnke and others 1969) and direct competition between oxygen and the inert gas did not appear to occur for an oxygenase (Doebbler and others 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Partly purified tyrosinase (PPO) was inhibited by noble gases including argon (Doebbler and others 1967; Behnke and others 1969; Spencer and others 1998; Zhang and others 2001). Ebert and Hornsey (1958) proposed that inert gases compete with oxygen for cellular sites; however, inhibition by noble gases was also found for some non‐oxygen dependant enzymatic reactions (Behnke and others 1969) and direct competition between oxygen and the inert gas did not appear to occur for an oxygenase (Doebbler and others 1967). Schreiner (1968) proposed that changes in enzymatic activity might be the result of interactions between the noble gases and the enzyme, but this theory was refuted by Behnke and others (1969) who concluded that high‐pressure inert gases inhibited tyrosinase activity in nonfluid systems by decreasing the availability of oxygen rather than by physically altering the enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation